Effects of reproductive strategies on pollutant concentrations in pinnipeds: a meta‐analysis. Issue 6 (24th April 2017) - Hitchcock, Daniel J.; Varpe, Øystein; Andersen, Tom; Borgå, Katrine
Abstract : In marine mammals such as pinnipeds (seals, sea lions and walruses), reproductive strategies reveal how species acquire, store and allocate energy to offspring. During lactation, females can allocate energy acquired from concurrent resources (income breeding); or utilize energy stored prior to reproduction (capital breeding). Mothers transfer a large proportion of energy to their pups via lipid rich milk, meaning that pollutants such as polychlorinated biphenyls (PCBs) and mercury (Hg) will also transfer, raising concern for negative health effects. To quantify the effect of reproductive strategy on maternal pollutant transfer in pinnipeds, we developed a proxy for income and capital breeding by focusing on the lactational component of reproduction, and arranged species along this gradient. We found a strong positive relationship between lipid content in milk and degree of capital breeding. We tested this gradient against maternal pollutant transfer expressed as a concentration ratio by meta‐analysis. In mother‐pup pairs, the concentration ratio of PCBs was one order of magnitude higher than for mercury. PCB concentrations in pups and juveniles were similar to adult females, but mercury was always lower in young offspring than in females. We found no effect of reproductive strategy between studies investigating mother‐pup pairs and non‐related females and juveniles (< 1 year old), however data were strongly biased towards capital breeders. Our results suggest that either: 1) reproductive strategy does not affect pollutant bioaccumulation; or 2) a lack of income breeder data prevents us from testing the overall effect of reproductive strategy on maternal pollutant transfer. The finding that PCB concentrations in juveniles are similar to females is of concern due to early life stage exposure. We recommend data collection from income breeding species such as the sea lions to elucidate whether reproductive strategy, and potentially other life history traits, has an overall effect on maternal pollutant transfer.